2007
DOI: 10.1093/sleep/30.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Practice Parameters for the Use of Actigraphy in the Assessment of Sleep and Sleep Disorders: An Update for 2007

Abstract: Recent research utilizing actigraphy in the assessment and management of sleep disorders has allowed the development of evidence-based recommendations for the use of actigraphy in the clinical setting. Additional research is warranted to further refine and broaden its clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
661
0
20

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,001 publications
(685 citation statements)
references
References 109 publications
4
661
0
20
Order By: Relevance
“…We also used a parallel group design in which the sleep restriction was compared to a control group with no change in sleep duration, rather than a cross-over design in which the effects of sleep restriction are compared to a period of recovery sleep-extension or recovery [19]. The aims in this study were, (i) To assess whether 10 sleep duration assessed using sleep diaries and actigraphy -a reliable and validated measure of sleep duration [20], could be manipulated adequately at home rather than in a controlled sleep-laboratory environment in healthy young men, (ii) to assess whether a smaller amount of sleep loss (1.5 hours), over a period of three weeks, has a an impact on insulin sensitivity as assessed through hyperinsulinaemic-euglycaemic clamp, the gold-standard approach and 15 (iii) to assess the time-course of the changes in sleep and metabolic parameters over the three week period.…”
Section: Introductionmentioning
confidence: 99%
“…We also used a parallel group design in which the sleep restriction was compared to a control group with no change in sleep duration, rather than a cross-over design in which the effects of sleep restriction are compared to a period of recovery sleep-extension or recovery [19]. The aims in this study were, (i) To assess whether 10 sleep duration assessed using sleep diaries and actigraphy -a reliable and validated measure of sleep duration [20], could be manipulated adequately at home rather than in a controlled sleep-laboratory environment in healthy young men, (ii) to assess whether a smaller amount of sleep loss (1.5 hours), over a period of three weeks, has a an impact on insulin sensitivity as assessed through hyperinsulinaemic-euglycaemic clamp, the gold-standard approach and 15 (iii) to assess the time-course of the changes in sleep and metabolic parameters over the three week period.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by several recent reviews and the newly updated practice parameters of the American Academy of Sleep Medicine (AASM) (Ancoli-Israel et al, 2003;Littner et al, 2003;Morgenthaler et al, 2007;Thorpy et al, 1995), actigraphy has been widely recognized as a low cost alternative to conventional PSG for screening of sleep disorders, with special emphasis on sleep-wake cycles and more specifically, insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of the first automatic scoring algorithm for actigraphy by Webster et al (1982), various computer algorithms have been developed to automatically score sleep and wake from the recorded raw actigraphy movement data (see Ancoli-Israel et al, 2003;Littner et al, 2003;Morgenthaler et al, 2007;Thorpy et al, 1995 for an extensive bibliography). Notable among the reported actigraphy algorithms are the ones developed by Sadeh et al (1989Sadeh et al ( , 1994Sadeh et al ( , 1995 covering not only adult normal and abnormal subjects, but also infants, the algorithm of Cole et al (1992), the Actigraph Data Analysis Software (adas) by Jean-Louis et al (1996), the algorithm reported by Sazonov et al (2004) and various commercially available algorithms accompanying the different actimeters available in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Actigraph was reported as a good method to obtain objective sleep data (Morgenthaler et al, 2007). Furthermore, it is worth to use in clinical set- tings, since it is easy to measure and score.…”
Section: Discussionmentioning
confidence: 99%
“…Actigraphy has been validated as a useful and sensitive method of measuring sleep status (Morgenthaler et al, 2007). Overall, sensitivity (0.965) and accuracy (0.863) of actigraphy were high (Marino et al, 2013).…”
Section: ) Sleep Disturbancementioning
confidence: 99%